ANALISIS KINERJA BANK BKE SETELAH DIAKUISISI MENJADI BANK SEABANK DENGAN MENGGUNAKAN UKURAN ROE DAN ROA - Anthony, Frankie; Gina Oktafiyanti; Elizabeth Tiur Manurung (Universitas Prof.Hazairin,SH Bengkulu, 2024)
The development of technology is currently felt by us, especially in the banking sector. Currently, there are many digital banks that are present around the Indonesian people to facilitate banking activities. One of the digital banks that are in great demand by the public is Bank Seabank. Bank Seabank is a bank that emerged from the acquisition of Bank BKE. The acquisition process that occurs in a company does not always go as expected. In this study, researchers will see how Bank BKE performed after being acquired into Bank Seabank. In this study, researchers used quantitative research methods with the aim of calculating whether there were significant changes when changing management from Bank BKE to Bank Seabank. In this study, Return on Assets and Return on Equity were also used as benchmarks for company performance. The result of this study is that after going through a management change from Bank BKE to Bank Seabank, no significant performance changes were found.